2007
DOI: 10.1074/jbc.m702350200
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Amino Acids Involved in Substrate Specificity of Methionine Sulfoxide Reductase A

Abstract: Methionine sulfoxide reductases (Msrs) are ubiquitous enzymes that catalyze the thioredoxin-dependent reduction of methionine sulfoxide (MetSO) back to methionine. In vivo, Msrs are essential in protecting cells against oxidative damages on proteins and in the virulence of some bacteria. There exists two structurally unrelated classes of Msrs. MsrAs are stereo-specific toward the S epimer on the sulfur of the sulfoxide, whereas MsrBs are specific toward the R isomer. Both classes of Msrs display a similar cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Second, the structure of the N. meningitidis MsrA active site, described as a "mirror" of the MsrB active site, revealed that the presence of the sulfenic acid in the catalytic Cys51 does not induce any conformational change within the active site, in particular at Trp53, whose role is equivalent to that of Trp65. 13,15,18 Recently, the NMR structure of Bacillus subtilis MsrB, which possesses the catalytic Cys117 and the recycling Cys63, was deposited in the PDB by Zhang et al (PDB ID 1XM0; unpublished results) from the "Northeast Structural Genomics" project (Target SR10). The 10 models available in the PDB file show that the loops are highly flexible (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Second, the structure of the N. meningitidis MsrA active site, described as a "mirror" of the MsrB active site, revealed that the presence of the sulfenic acid in the catalytic Cys51 does not induce any conformational change within the active site, in particular at Trp53, whose role is equivalent to that of Trp65. 13,15,18 Recently, the NMR structure of Bacillus subtilis MsrB, which possesses the catalytic Cys117 and the recycling Cys63, was deposited in the PDB by Zhang et al (PDB ID 1XM0; unpublished results) from the "Northeast Structural Genomics" project (Target SR10). The 10 models available in the PDB file show that the loops are highly flexible (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Altogether, these results are consistent with the recent enzymology studies done by our group. 22 In that context, the structural/molecular factors that contribute to the better binding of protein-bound MetSO rather than free MetSO remain to be characterized.…”
Section: Substrate Bindingmentioning
confidence: 99%
“…Recently, amino acids involved in the substrate specificity and in the catalysis of the reductase step of the N. meningitidis MsrA domain have been characterized by molecular enzymology approaches. 15,22 A scenario of the catalysis of the reductase step has been proposed. 15 In all the X-ray structures determined so far, the distance between Cys51 and Cys198 is too large to allow the formation of an intramolecular disulfide bridge.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, it is clear that the presence of the sulfoxide function is a prerequisite for binding to both MSRs. The active sites of MSRA and MSRB are both located on the surface of the enzymes and contain two mirror-image sub-sites which confer stereospecificity for the R or S stereoisomer of L-Met-O: (1) a hydrophilic pocket involving the stabilization of the protonated sulfoxide function of the substrate via hydrogen bonding; and (2) a hydrophobic pocket consisting essentially of the side chain of a Trp residue, which stabilizes the ε-methyl group of the substrate via its indole ring ( Figure 4 ) [ 9 , 13 , 28 , 29 ]. The selectivity of the enzymes for protein-bound Met-O versus free Met-O probably derives from a destabilizing effect, due to repulsive interactions with the charged amino and/or carboxyl groups of the free amino acid.…”
Section: Methionine Sulfoxide Reductase Activities Of Pilbmentioning
confidence: 99%